CSF flow measurement in the mesencephalic aqueduct using 2D cine phase-contrast MRI in dogs with communicating internal hydrocephalus, ventriculomegaly, and physiologic ventricular spaces - Farke, Daniela; Dörn, Francesca; Schaub, Sebastian; Wenz, Ella; Büttner, Katharina; Schmidt, Martin J. (Frontiers in Veterinary Science, 2024)
BackgroundBrachycephalic dogs are overrepresented with ventricular enlargement. Cerebrospinal fluid (CSF) flow dynamics are not completely understood. MRI techniques have been used for the visualization of CSF dynamics including phase-contrast imaging.ObjectivesThis study aimed to determine a causality between CSF flow and ventriculomegaly or hydrocephalus and to compare CSF flow dynamics among dogs with ventriculomegaly, internal hydrocephalus, and physiologic ventricles.AnimalsA total of 51 client-owned dogs were included in the study.MethodsMagnetic resonance imaging (MRI)-based FLASH sequences and phase-contrast images of the brain were obtained, and the ROI was placed at the level of the mesencephalic aqueduct. ECG monitoring was performed parallel to MRI acquisition. Evaluation of flow diagrams and processing of phase-contrast images were performed using commercially available software (Argus VA80A, Siemens AG Healthcare Sector, Erlangen, Germany). Dogs were divided into three groups: Group 1 consisted of brachycephalic dogs with ventriculomegaly (group 1A) or internal hydrocephalus (group 1B), group 2 consisted of brachycephalic dogs with normal ventricles, and group 3 consisted of meso- to dolichocephalic dogs with normal ventricles.ResultsGroup 1 had a higher median Vrost (4.32 cm/s; CI: 2.94–6.33 cm/s) and Vcaud (−6.1 cm/s, CI: 3.99–9.33 cm/s) than group 2 (Vrost: 1.99 cm/s; CI 1.43–2.78 cm/s; Vcaud: 2.91 cm/s, CI: 2.01–4.21 cm/s; p = 0.008; p = 0.03) and group 3 (Vrost:1.85 cm/s, CI: 1.31–2.60 cm/s; Vcaud − 2.46 cm/s, CI 1.68–3.58 cm/s; p = 0.01; p = 0.02). The median Volcaud of group 1 (−0.23 mL/min, CI: 0.13–0.42 mL/min) was higher than that of group 2 (−0.09 mL/min, CI: 0.05 mL/min and 0.15 mL/min) (p = 0.03). Groups 1A and 1B did not differ in Vcaud, Vrost, Volcaud, and Volrost. Group 1A and 1B showed a higher median Vrost (4.01 cm/s, CI: 2.30–7.05 cm/s; 5.94 cm/s, CI: 2.16–7.88 cm/s) than group 2 (1.85 cm/s, CI: 1.24–2.80 cm/s.) (p = 0.03; p = 0.004).Conclusion and clinical importanceIncreased CSF flow velocities in rostral and caudal directions are present in dogs with ventriculomegaly and internal hydrocephalus compared to normal controls.